Cloning and expression of Aujeszky's disease virus glycoprotein E (gE) in a baculovirus system - Dambros, Régia Maria Feltrin (2007)
Aujeszky' s disease (AD) is an infectious disease causing important economic losses to the swine industry worldwide. The disease is caused by an alpha-herpesvirus, Aujeszky' s disease virus (ADV), an enveloped virus with a double stranded linear DNA genome. The ADV genome encodes 11 glycoproteins, which are major targets for the immune system of the host in response to the infection. The glycoprotein E (gE) is a non-essential protein and deletion of the gE gene has been used for the production of marker vaccines. Aiming to develop molecular reagents for the production of a gE specific ELISA test, the gE gene was amplified by PCR, cloned and expressed into a baculovirus expression system. The recombinant DNA vector pFastBac-gE-ADV was used for site-specific transposition into the recombinant baculovirus (bacmid). Colonies with recombinant bacmid-pFastBac-gE-ADV were selected by antibiotic and color selection and the presence of the gE gene was confirmed by PCR. The recombinant bacmid-pFastBac-gE-ADV was cotransfected in insect Trichoplusia ni and the presence of the recombinant DNA and gE protein were detected by PCR, SDS-PAGE and Western blotting, respectively.